THE EFFECTS OF JOB STRESS AND COMPENSATION ON EMPLOYEE TURNOVER INTENTION AS MEDIATED BY ORGANIZATIONAL COMMITMENT (At Dinas Pariwisata and Kebudayaan DKI Jakarta) - Saryanti, Silfi Defi; Lo, Singmin Johanes (International Humanities and Applied Science Journal, 2021)
This study aims to analyse the effects of Job Stress and Compensation on employee Turnover Intention as mediated by Organizational Commitment. The populations in this research are 147 permanent employees of Dinas Pariwisata and Kebudayaan DKI Jakarta. The research samples are 89 respondents by using Slovin’s formula with 5% error tolerance. The sampling method used is a quota sampling taken proportionally for each level. The method of data collection uses questionnaires. Data are analysed using SEM SmartPLS version 3.2.8 for Windows. The results of this research show that: (1) Job stress has a positive and significant influence on employee turnover intention; (2) Compensation has a positive, but not significant influence on employee turnover intention; (3) Job stress has a negative and significant influence on employee organizational commitment; (4) Compensation has a positive and significant influence on employee organizational commitment; (5) Organizational commitment has a negative and not significant influence on employee turnover intention; (6) Organizational commitment does not significantly mediate the influence of job stress on employee turnover intention; and (7) Organizational commitment does not significantly mediate the influence of compensation on employee turnover intention.